Role of Frequency Doubled Nd: Yag Laser in Treatment of Corneal Neovascularisation - Kumar, Jitendra (J Clin Diagn Res, 2016)
INTRODUCTION: Cornea is the outermost transparent coat of eye along with sclera, for which its avascularity is essential for maintaining its transparency to have normal visual acuity. Corneal neovascularization is characterized by the invasion of new blood vessels into the cornea from the limbus interfering with corneal transparency, resulting in reduction in visual acuity. It also increases the risk of graft rejection. So their being a dire need to treat corneal neovascularisation, with laser photocoagulation being an effective means of treating it. AIM: To evaluate the efficacy and safety of frequency doubled Nd:Yag laser photocoagulation in treatment of corneal neovascularisation. MATERIALS AND METHODS: A single centre prospective study was carried out on patients attending the outpatient department of ophthalmology in Maharani Laxmi Bai Medical College, Jhansi. Forty eyes of 40 patients having corneal neovascularisation with quiescent eyes satisfying the inclusion criteria were selected and treated with laser. The efficacy of the procedure was noted in terms of area of corneal neovascularisation, status of treated vessels, area of corneal opacity, visual acuity. The above parameters of selected patients were recorded before treatment and subsequent follow up visits at 1 week, 1 month, 2 month and 3 month after laser. Paired t-test was used to calculate the p-value. RESULTS: There was a statistically significant difference in the percentage mean area of corneal neovascularisation with a pre laser value of 31.93% to 17.62% after 3 months of laser treatment (p-value<0.0001). The percentage mean area of corneal opacity decreased from 30.75% to 23.74% (p<0.0001). Out of 185 corneal vessels, 99 (53.51%) vessels were completely occluded,17(9.18%) vessels were partially occluded and 69(37.29%) vessels were recanalised at the end of 3 months after laser treatment. CONCLUSION: Frequency doubled Nd:Yag laser is an effective and safe method for the treatment of corneal neovascularisation.